Neurological complications of breast cancer: A prospective cohort study. Issue 5 (October 2015) - Pereira, Susana; Fontes, Filipa; Sonin, Teresa; Dias, Teresa; Fragoso, Maria; Castro-Lopes, José Manuel; Lunet, Nuno
Abstract Objectives Neurological complications secondary to breast cancer treatment may be an important contributor to these patients morbidity. We aimed to quantify the incidence of neurological complications of breast cancer treatment during the first year after diagnosis. Materials and methods We performed a prospective cohort study with 506 patients recruited at the Portuguese Institute of Oncology of Porto, among those newly diagnosed. Participants underwent a neurological examination before treatment, after surgery, after chemotherapy (whenever applicable) and at one year after enrollment. The Montreal Cognitive Assessment was used to assess cognitive function, at baseline and at one year. We computed one-year cumulative incidence estimates and the corresponding 95% confidence intervals (95%CI) for each of the neurological complications. Results Just over half of women had breast cancer stage 0 or I. A total of 6.9% were submitted to neoadjuvant chemotherapy but most of them completed adjuvant treatment – endocrine therapy, radiotherapy or chemotherapy (83.9%, 73.0% and 52.5%, respectively). The cumulative incidence of at least one oncological-related neurological complication during the first year after diagnosis was 48.4% (95%CI: 44.1–52.8); the most frequent were neuropathic pain (30.8%, 95%CI: 27.0–35.0), chemotherapy-induced peripheral neuropathy (16.8%, 95%CI: 13.8–20.3), phantom breast pain/syndrome (16.6%, 95%CI: 13.6–20.1) and cognitive decline (8.1%, 95%CI: 5.8–11.1). Conclusions Neurological complications were a frequent side-effect of breast cancer management in the first year after diagnosis, especially neuropathic pain and chemotherapy-induced peripheral neuropathy. Accurate diagnosis and treatment of these complications are important to minimize the burden associated with breast cancer treatment in breast cancer survivors.